Development of SIKAP SeBeNingMaS LMS-Based SOP and Adaptive Interface to Enhance Holistic Learning in Social Studies - Hamdan Hamdan; Parji Parji; Muhammad Hanif (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study developed and evaluated the SIKAP SeBeNingMaS best practice package: an SOP for character habituation, a Microsoft Teams LMS interface designed with user‑centered design, and instructional modules adopting 21st Century Learning Design for Social Studies at SMPN 10 Madiun. The Research and Development (R&D) followed the ADDIE framework. Data collection included observation, interviews, expert validation questionnaires, prototype trials (alpha and beta), FGDs, and pretest–posttest assessments; analyses combined qualitative methods and quantitative statistics (SPSS). Results indicated the product was valid and practical: expert validation rated it Very Feasible (mean ≈ 4.55/5), teachers rated it Very Practical (mean ≈ 4.50/5), and student acceptance ranged 4.05–4.30/5. Pretest–posttest in a broad‑limited trial (n = 514) showed mean gains of ≈ +8.2 points with a large effect size. Qualitative findings corroborated that the SOP ritual strengthened affective dimensions while the UCD interface eased navigation, sped assignment workflows, and improved feedback quality. The product is usable, useful, and adoptable at limited scale with strong potential for multilocation replication given infrastructure, tiered training, and robust data governance